Evidence that the Herpes Simplex Virus Type 1 ICP0 Protein Does Not Initiate Reactivation from Latency In Vivo - Thompson, R. L. (American Society for Microbiology, 2006)
The stress-induced host cell factors initiating the expression of the herpes simplex virus lytic cycle from the latent viral genome are not known. Previous studies have focused on the effect of specific viral proteins on reactivation, i.e., the production of detectable infectious virus. However, identification of the viral protein(s) through which host cell factors transduce entry into the lytic cycle and analysis of the promoter(s) of this (these) first protein(s) will provide clues to the identity of the stress-induced host cell factors important for reactivation. In this report, we present the first strategy developed for this type of analysis and use this strategy to test the established hypothesis that the herpes simplex virus ICP0 protein initiates reactivation from the latent state. To this end, ICP0 null and promoter mutants were analyzed for the abilities (i) to exit latency and produce lytic-phase viral proteins (initiate reactivation) and (ii) to produce infectious viral progeny (reactivate) in explant and in vivo. Infection conditions were manipulated so that approximately equal numbers of latent infections were established by the parental strains, the mutants, and their genomically restored counterparts, eliminating disparate latent pool sizes as a complicating factor. Following hyperthermic stress (HS), which induces reactivation in vivo, equivalent numbers of neurons exited latency (as evidenced by the expression of lytic-phase viral proteins) in ganglia latently infected with either the ICP0 null mutant dl1403 or the parental strain. In contrast, infectious virus was detected in the ganglia of mice latently infected with the parental strain but not with ICP0 null mutant dl1403 or FXE. These data demonstrate that the role of ICP0 in the process of reactivation is not as a component of the switch from latency to lytic-phase gene expression; rather, ICP0 is required after entry into the lytic cycle has occurred. Similar analyses were carried out with the ΔTfi mutant, which contains a 350-bp deletion in the ICP0 promoter, and the genomically restored isolate, ΔTfiR. The numbers of latently infected neurons exiting latency were not different for ΔTfi and ΔTfiR. However, ΔTfi did not reactivate in vivo, whereas ΔTfiR reactivated in ∼38% of the mice. In addition, ICP0 was detected in ΔTfiR-infected neurons exiting latency but was not detected in those neurons exiting latency infected with ΔTfi. We conclude that while ICP0 is important and perhaps essential for infectious virus production during reactivation in vivo, this protein is not required and appears to play no major role in the initiation of reactivation in vivo.